Tolosa-Hunt syndrome: a rare case report with uncommon imaging findings and discussion - Ranjan, Rajeev; Banerjee, Arnab; Sarkar, Ramita; Sarkar, Niladri (International Journal of Research in Medical Sciences, 2017)
A 45 year old diabetic but non hypertensive female presented with unilateral ptosis and complete external ophthalmoplegia on the left side. All the routine investigations were inconclusive. A signal void change was found in MRI study including angiogram of brain. On performing VEP (visually evoked potential), there was mild left optic pathway dysfunction (axonal and demyelinating). A probable diagnosis of Tolosa-Hunt Syndrome (THS) was made and the patient was started on steroids. She responded dramatically to the therapy and was discharged on steroids. Thus the diagnosis of THS was confirmed. On follow up after one month, both her ptosis and ophthalmoplegia had resolved completely. On subsequent follow up visits, she was free of any ophthalmological symptoms and signs.